Investigation of the English as a medium of instruction as a pedagogical technology in university educational activities - Litovchenko, V I; Shmeleva, Zh N (Journal of physics. Conference series, 2020)
In 2020 the world has faced the pandemic situation with COVID-19 that caused a vast amount of challenges for many spheres of human life including the system of higher education. Students and faculty members of higher educational institutions were forced to critically change their learning style using distant technologies, Zoom and Moodle platforms which was not always perceived positively. Nevertheless, the existing situation of restrictions revealed larger opportunities for an increase in English learning and education through English. One of the most popular directions is English as a medium of instruction (EMI). The international character and popularity of English are undisputable, that's why it is widely used to teach specific subjects in non-native English-speaking countries. Institutions of higher education all over the world start offering educational programs in English for disciplines in different training directions whether it is management or agriculture. The article aims at focusing on implementing EMI in two institutions of higher education in the Siberian Federal District where faculty members teach in English within modern European internationalization trend of offering courses and Master degree programs in English. The authors make an attempt to reveal advantages and disadvantages of EMI implementation and introduction. Based on the works and experiments of foreign scientists and having some experience in using English as a medium of instruction, the authors draw the conclusion that the EMI implementation in its pure form has certain imperfections. Consequently, the authors suggest the set of measures to make this process more effective: first, to search for opportunities for the foreign language additional study by students in the Bachelor's degree, via elective courses, or Language Learning Business Centers; secondly, to use the so-called CLIL-ised EMI; thirdly, to provide faculty members with English-training courses and ensure the access to the resources for the development of methodological materials.